2019
DOI: 10.3389/fnut.2018.00138
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 2 Study to Assess the Immunomodulatory Capacity of a Lecithin-based Delivery System of Curcumin in Endometrial Cancer

Abstract: Curcumin is a botanical with anti-tumor and immunomodulatory properties. We hypothesized that curcumin supplementation might influence inflammatory biomarker levels in endometrial carcinoma (EC). In this open-label, non-randomized phase 2 study (NCT02017353), seven EC patients consumed 2 g/day Curcumin Phytosome (CP) orally for 2 weeks. Blood was taken at baseline, days 1, 7, 14, and 21. The following analytes were measured: curcuminoids and metabolites, 56 inflammatory biomarkers, COX-2, frequencies of myeloi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Overall findings suggest modest immunomodulatory effects of CP in EC. 238 The effects of CUR (10-60 μM) on the T cell subtype of the immune system showed moderately enhanced IL-4 production, although IL-2 production remained unchanged. Moreover, the development of CTL was also unaffected in cancer patient.…”
Section: Immunomodulatory Effects Of Curcumin Clinical Studiesmentioning
confidence: 96%
“…Overall findings suggest modest immunomodulatory effects of CP in EC. 238 The effects of CUR (10-60 μM) on the T cell subtype of the immune system showed moderately enhanced IL-4 production, although IL-2 production remained unchanged. Moreover, the development of CTL was also unaffected in cancer patient.…”
Section: Immunomodulatory Effects Of Curcumin Clinical Studiesmentioning
confidence: 96%
“…Furthermore, cichoric acid from echinacea promoted phagocytic activity, both in vitro and in vivo [ 53 ]. Anti-inflammatory and immune-modulatory effects has been highlighted for curcumin too, although the poor bioavailability limits its clinical application [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, clinical studies of phytoestrogens combined with cancer treatments are underway to observe if there is a synergistic effect to treat cancer. Here, we have reviewed 18 clinical trials [61,[227][228][229][230][231][232][233][234][235][236][237][238][239][240][241][242][243][244], conducted between 2002 to present, focused on breast cancer (seven trials) [227][228][229][230][231][232][233][234], prostate cancer (eight trials) [61,[235][236][237][238][239][240][241], endometrial cancer (two trials) [242,243], and colon cancer (two trials) [240,244], combined with two categories of phytoestrogens treatments: fruits/whole grains/seeds such as resveratrol and curcumin (eight trials) and soy isoflavones such as GEN (10 trials) (Table 3 and Supplementary Table S1).…”
Section: Application Of Phytoestrogens In the Prevention Or Treatment Of Cancers: Evidence From Clinical Trialsmentioning
confidence: 99%
“…Phytoestrogens alter cancer-related gene expression profiles in breast cancer (NCT00597532, NCT00290758, and University of North Dakota School of Medicine and Health Sciences trail), prostate cancer (NCT00546039), endometrial cancer (NCT02017353), and colon cancer (NCT00256334). More interestingly, some of the trials have shown that phytoestrogens are altering the cancer-related gene expression profiles [227,233,238,243,244]. Under the concept of personalized medicine, gene expression analyses could be an alternative and cost-effective way to predict the effectiveness of phytoestrogens in cancer prevention and treatments.…”
Section: Application Of Phytoestrogens In the Prevention Or Treatment Of Cancers: Evidence From Clinical Trialsmentioning
confidence: 99%